Strategy and cost stickiness under different managerial abilities: Evidence from Southeast Asia - Mitha Dwi Restuti; Lindawati Gani; Elvia R. Shauki; Lianny Leo (Cogent Business & Management, 2022)
Firms' strategies reflect their competitive advantages, such as the prospector focuses on innovation and defenders focus on cost efficiency. The differences in strategies' competitive advantages imply different resource management to different magnitude of cost stickiness. This study examined whether prospectors and defenders exhibit different magnitude of cost stickiness. This study also examines cost stickiness differences in high and low managerial abilities for prospector and defender. The study investigates 24,362 firm-year observations in six Southeast Asian countries in 2013-2019. The results show that Southeast Asian firms exhibit cost stickiness. Both prospectors and defenders exhibit cost stickiness, likely because Southeast Asian firms mostly operate in raw goods trading and do not innovate much in high technology. Consequently, prospectors do not exhibit different cost behavior than defenders. Our findings document that firms led by less able managers exhibit greater cost stickiness, both for prospectors and defenders. The results suggest that managerial characteristics remain crucial in resource management, because less able managers tend to retain resources to cope with operational problems and meet future sales demands.
Keywords: 650; cost stickiness; defender; managerial ability; prospector; Southeast Asia; strategy